Comparative safety analysis of Riluzole, Edaravone and Tofersen in ALS management: insights from FAERS database - Guan, Shuang; Wang, Sicun; Shi, Yinli; Leng, Yuanyuan; Ming, Yu; Hou, Zhiyong; Yu, Yanan; Wang, Zhong; Liu, Jun (Frontiers in Pharmacology, 2025)
BackgroundAmyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder. Riluzole, Edaravone, and Tofersen, three promising treatments, have distinct profiles that merit comparative analysis to guide clinical decision-making.MethodsThis study utilizes a pharmacovigilance analysis of adverse events reported in the FDA Adverse Event Reporting System database from Q1 2004 to Q2 2024. Employing disproportionality, we assessed and compared the AE signals associated with Riluzole, Edaravone, and Tofersen to elucidate their safety profiles in ALS treatment. Finally, applying the Random Walk with Restart (RWR) algorithm to the protein-protein interaction (PPI) network for selecting drug target genes that have a strong correlation genes associated with severe adverse reactions. Finally, their interactions with the target were assessed through molecular docking and transcriptome analysis.ResultsThe analysis included 2106 AE reports for Riluzole, 2466 AE reports for Edaravone, and 136 for Tofersen. Highlights the higher incidence of adverse reactions associated with Riluzole, including abdominal discomfort, hypoaesthesia oral, and hepatic enzyme increased, as well as a significant correlation between Edaravone and falls, gait disturbance, and aphasia. Tofersen exhibits different adverse reactions compared to Riluzole and Edaravone, such as headaches, csf red blood cell count positive. Comparative analysis revealed that the three drugs shared a serious adverse reaction, which is thrombosis. RWR analysis identified seven targets related to thrombosis caused by the three drugs, including F10 and MMP9. Subsequently, molecular docking and transcriptome analysis indicate a favorable binding interaction between the drug candidate and the F10 molecule.ConclusionThis comprehensive evaluation underscores the importance of understanding the distinct AE profiles of Riluzole, Edaravone, and Tofersen in clinical practice, providing valuable insights for personalized ALS management. Future research with rigorous prospective designs is recommended to validate these findings and explore the mechanisms underlying the reported adverse events.